Análise dos modos e efeitos de falha do processo de vulcanização em uma indústria automotiva - Martini, Júlia de Assis (2017)
Reliability in the quality of the product by the customers can be great difference of the companies in search of success in the market. All involved in the process seek, in different ways, eliminate or reduce as failures that interfere with the final quality. Production engineering enables you to intelligently apply your tools to act positively on your company's bottom line. In this study, tools of the Production Engineering were applied for an analysis of the vulcanization process in an automotive industry. First, the Process Mapping was carried out for the knowledge of the sectors and the operations, then a Critical Process Analysis by Experts for the determination of the studied area, and with the data collected, the FMEA was applied. With the result obtained, were identified critical process failures and proposed solutions were to minimize failures.